'Surprise': Outbreak of Campylobacter infection associated with chicken liver pâté at a surprise birthday party, Adelaide, Australia, 2012 - Emma Denehy; Amy Parry; Emily Fearnley (World Health Organization Regional Office for the Western Pacific, 2012)
Objective: In July 2012, an outbreak of Campylobacter infection was investigated by the South Australian Communicable Disease Control Branch and Food Policy and Programs Branch. The initial notification identified illness at a surprise birthday party held at a restaurant on 14 July 2012. The objective of the investigation was to identify the potential source of infection and institute appropriate intervention strategies to prevent further illness.Methods: A guest list was obtained and a retrospective cohort study undertaken. A combination of paper-based and telephone questionnaires were used to collect exposure and outcome information. An environmental investigation was conducted by Food Policy and Programs Branch at the implicated premises.Results: All 57 guests completed the questionnaire (100% response rate), and 15 met the case definition. Analysis showed a significant association between illness and consumption of chicken liver pâté (relative risk: 16.7, 95% confidence interval: 2.4-118.6). No other food or beverage served at the party was associated with illness. Three guests submitted stool samples; all were positive for Campylobacter. The environmental investigation identified that the cooking process used in the preparation of chicken liver pâté may have been inconsistent, resulting in some portions not cooked adequately to inactivate potential Campylobacter contamination.Discussion: Chicken liver products are a known source of Campylobacter infection; therefore, education of food handlers remains a high priority. To better identify outbreaks among the large number of Campylobacter notifications, routine typing of Campylobacter isolates is recommended.